Theory and Practice of Climate Adaptation (Climate Change Management,, 2018)
Climate change is one of the greatest challenges of our time. As such, both the Fifth Assessment Report (AR5) released by the Intergovernmental Panel on Climate Change (IPCC) and the 25th Conference of the Parties (COP 25) recommendations call for action not only from government, but also from various stakeholders. Apart from the knowledge offered by modeling and forecasts, which allows the readers to understand the problem and how it is likely to develop in the future, the book highlights approaches, methods and tools that can help readers cope with the social, economic and political problems posed by climate change. In other words, the book's goal is to accelerate developments in the field of climate change adaptation. This book gathers papers presented at the "2nd World Symposium on Climate Change Adaptation", a joint initiative by the University of Coimbra (Portugal), the Research and Transfer Centre "Sustainable Development and Climate Change Management" at Hamburg University of Applied Sciences (Germany), and the International Climate Change Information Programme (ICCIP). The book is truly interdisciplinary, covering various key areas in the field of climate change adaptation. Its focus is on "integrative approaches to implementing climate change adaptation", and is expected to contribute to the further development of this fast-growing field.